Physalis peruviana: A profitable cash crop for small farmers - Pagare, Saurabh; Kumar, Bhumesh; Jaggi, Disha; Singh, P K (Indian Farming, 2019)
Ensuring food security ought to be an issue of great importance for a country like India where about one-third of the population is estimated to be absolutely poor and malnourished in one way or another. Food availability and accessibility are necessary conditions for food security. Due to changes in consumption patterns, demand for fruits, vegetables, and other food products has been increasing, hence, there is a need to increase crop diversification. Adoption/domestication of wild/ weedy species which are nutritionally sound, environmentally well adapted and locally acceptable will go a long way in alleviating malnutrition and ensuring food security with dietary diversity. Address to above problems will definitely pave the way towards achieving food security with acceptable nutritional status. There is untapped potential for increasing the range of food products suitable for human consumption. Farmers should be encouraged for commercial cultivation of locally available plant species which yet to be recognized as a crop. Cultivation of Physalis peruviana (Rashbhari) is a viable and one of the profitable options for small farmers and may be helpful in realizing Hon’ble Prime Minister’s Vision Doubling Farmers’ Income by 2022.